Quality management systems, employee satisfaction and motivational factors influence on employee performance in private higher education institutions in Malaysia - Norreha, Norreha Othman (2019)
Education is one of the important key areas of transforming Malaysia from a moderate income country to a high income country. Both public and private higher education institutions (HEI) need to work together to achieve the goal. Thus, the aim of this research is to examine the relationship between quality management systems (QMS) of private HEI which implement QMS ISO 9001:2008 towards the employee performance. This study also examined the effects of an employee satisfaction as a mediator and motivational factors as a moderator of the study relationships. Three main theories (System theory, Utility theory and Herzberg theory) have been used to explain the possible relationship between variables in the framework proposed. This study adopted quantitative approaches to obtain survey data and used proportionate stratified random sampling. There were 450 questionnaires which had been sent to private HEI, 222 were received and only 202 questionnaires were used for statistical analysis purposes with the response rate of 61%. The target respondents were academic staffs of the private HEI. After obtaining the data, descriptive analysis was done using SPSS, and inference analysis using software SmartPLS. The findings show that there is a significant relationship between QMS and the employee performance (management responsibility, resource management, product realization and measurement, analysis and improvement). The study also revealed that the mediating variable of employee satisfaction influenced the relationship between QMS and employee performance. However, the motivational factors did not act as a moderating variable between the relationship of QMS and the employee satisfaction. The results of the study could contribute to enhance knowledge on individual variable or a relationship between QMS, employee satisfaction, motivational factors and employee performance.